Ecological Adaptation Patterns to Tropical Climate Change Phenomena in Climate-Resilient Potato Crop Engineering - Bae, Sairuddin; Demmalino, Eymal Bahsar; Tahara, Tasrifin; Yassi, Amir; Darhamsyah, . (Engineering, Technology & Applied Science Research, 2025)
Climate change has a significant impact on tropical agricultural systems, particularly in potato cultivation, which is highly sensitive to environmental fluctuations. This study aims to analyze ecological adaptation patterns in potato crop engineering to enhance resilience against the impacts of tropical climate change. A mixed-methods approach was employed, combining field observations, climate data analysis, and controlled environment experiments to evaluate plant responses to varying climatic conditions. The results indicate that fluctuations in temperature, irregular rainfall, and increased humidity have a significant impact on potato growth, yield, and disease susceptibility. Adaptation strategies, such as selecting climate-resilient potato varieties, optimizing irrigation management, and implementing soil conservation techniques, were found to mitigate the negative effects. Based on these findings, this study suggests incorporating climate-resilient crop engineering into sustainable agricultural policies to ensure long-term food security in tropical regions.